Effect of herbal immunomodulators on immune status, haematological and serum biochemical parameters of Japanese quails (Coutrinix japanica) during summer stress - RAJU, S; GURRAM, SRINIVAS; BORA, SWATHI; KUMAR, B SAMPATH (The Indian Journal of Animal Sciences, 2019)
As the body temperature of birds rise, growth and production parameters tend to decline. In order to address the problem of heat stress, an experiment was conducted to investigate the effect of different herbal immunomodulators on the haemobiochemical and immune status of Japanese quails. Japanese quails (Coutrinix japanica) (120; day-old) were randomly divided into 4 treatment groups, viz. T1 (control diet), T2 (Stressroak liquid), T3 (Withania somnifera and Phyllanthus emblica liquid), T4 (Glycrrhiza glabra, Tribulus terrestris and Asparagas racemosus liquid) with 6 replicates of 5 birds each. The haematological data revealed that total erythrocyte count, packed cell volume, haemoglobin, mean corpuscular volume and mean corpuscular haemoglobin were significantly high in all test groups (T2, T3 and T4) compared to control. Total leukocyte count, mean corpuscular haemoglobin concentration, total serum protein, albumin, globulin, A/G ratio, triglycerides, cholesterol and blood glucose were not affected by herbal immunomodulators at 5th week of age. Immune response as revealed by delayed type of hypersensitivity (measurement of skin thickness) and serum immunoglobulin were significantly high in all the test groups compared to control. It can be concluded that herbal immune modulators improve haemotological and immune status of Japanese quails without affecting serum biochemical parameters.